Efektivitas Penggunaan Model Pembelajaran TPS Berbantuan Media Komik Terhadap Hasil Belajar Ekonomi Siswa Kelas XI Di SMA Bina Putra Tangerang - Aulia Luqmansyaf; Syafaatul Hidayati (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2021)
This study examined the effectiveness of the use of the TPS learning model with the help of comic media on the economics subject learning outcomes of XI grade students at SMA Bina Putra. The technique used in this exploration was Quasi Experiment using Non Equivalent Control Group Design. The population in this study were students of class XI SMA Bina Putra first semester in the Academic Year 2021/2022 with a total sample of 45 students as respondents. The research method used in this research was a quasi-experimental method. Experimental quasi-experimental research was a process of scientific investigation to find the effect of a certain treatment by comparing the conditions before and after being given the treatment or by comparing the samples that were given the treatment and those who were not given the treatment (the control sample). The results showed that the cognitive learning outcomes after using the Think Pair Share learning model assisted by the Media Comics Experimental class were normally distributed with the content value of the experimental class learning outcomes 0.80 > 0.05, meaning that Hᴏ was accepted with an average value of 76.13; (2) classical mastery as a result of the student's economics study in class XI Experiment at SMA Bina Putra was 75%; and (3) the average result of the Experiment and Control class was higher than the Experiment class, where the experimental class was 76.13 while the Control class was 71.36.